Swarm intelligence.: (Principles, current algorithms and methods) (Control, robotics and sensors series, 2018)
Covering principles and known approaches through to new research developments, analyses and applications of typical swarm intelligence methods, the aim of this three-volume book set is to provide readers with a full view of the field of swarm intelligence. In volume 1, the authors introduce the basic principles of well-known swarm intelligence algorithms and efficient improvements (from typical PSO, ACO and swarm intelligence algorithms to swarm robotics methods).